Proceedings of the 1st Public Health International Conference (PHICo 2016) 2017
DOI: 10.2991/phico-16.2017.39
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Self Care Behavior and the Level of Hba1c of the Patients with Diabetes Mellitus Type 2 in Binjai City, Sumatera Utara Province

Abstract: Abstract-Diabetes has become the fastest growing chronic disease in the world. Therefore, in order to manage it, behavioral changes in lifestyle including physical activity, dietary, monitoring of blood glucose levels (BGL), and obedience to treatment are needed. A good self care (self-management) of patients with diabetes will help them manage the disease. American Association of Diabetes (ADA) suggest people with diabetes type 2 to have selfcare behaviors that can improve their quality of life while reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…Good self-care score is zero. This finding was in line with other researches[ 10 17 18 19 ] that the majority of patients belong to low level self-care group. This show that poor self-care behaviors in DM patients exist nearly in all countries.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Good self-care score is zero. This finding was in line with other researches[ 10 17 18 19 ] that the majority of patients belong to low level self-care group. This show that poor self-care behaviors in DM patients exist nearly in all countries.…”
Section: Discussionsupporting
confidence: 93%
“…Also this study concluded that there was a correlation between self-care behaviors and HbA1C levels that is agreement with previous research. [ 6 10 17 18 19 21 22 ] Therefore Self-care behavior is necessary for patients with type 2 diabetes because help patients improve their blood glucose control. Another study investigated the difference between DM patients who performed only treatment orders and those who performed both healthy behavior and medical therapy found that self-care behaviors lead to better adherence to treatment than patients who perform medical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were consistent with previous studies reporting that depression is associated with poor glycemic control in patients with T2DM [13, 34-37]. In line with previous studies, we found a negative association between HbA1c and self-efficacy as well as self-management behaviors ( p < 0.01) [21, 38]. To delve deeper into the complex relationship between depression, self-efficacy, self-management behaviors, and HbA1c, series of hierarchical linear regression analyses were conducted, after controlling for the covariates.…”
Section: Discussionsupporting
confidence: 93%